Nutritional education in elementary schools of Guarulhos-sp - Assunção Iuliano, Bianca; Cervato Mancuso, Ana Maria; Dianezi Gambardella, Ana Maria (O Mundo da Saúde, 2009)
This work aims to describe nutritional education activities in elementary schools of the city of Guarulhos. A descriptive survey was done with a qualitative approach in 20% of elementary schools of Guarulhos by means of an exhaustive semi-structured interview with principals and coordinators. The reading of answers was done by means of Thematic Analysis of Content, categorizing nutritional education activities carried through with students according to pedagogical strategies, used subjects and resources. The results identified 23 different strategies in the 13 studied schools. There is an emphasis in Informal Instructions by Teachers during School Meals and Lessons in all schools. They approach subjects such as Alimentary Habits and Health, and the Menu is the main resource. The school with more varieties of strategies mobilized the school community to maintain a truck farm as a base of its pedagogical project. We also observed that the distribution of school meals in the city was changed to a self-service format. We conclude that initiatives are isolated and in general predominating in information giving, in detriment of a significant and participative education, as well as playful.